Knowledge Management for Electronic-Based Government System Using Semantic Thesaurus - Nuraisa Novia Hidayati; Agoeng Srimoeljanto (Faculty of Computer Science - Universitas Indonesia, 2023)
Sistem Pemerintahan Berbasis Elektronik (SPBE), the electronic-based government system, is Indonesia’s egovernment policy providing services to citizens through information and communication technology. Knowledge containing SPBE must be managed in various ways, one of which is the creation of an SPBE thesaurus to facilitate access and search for SPBE-related items using words or terms about it. In this study, we provide an overview of the thesaurus development process that has complied with the ISO 25964 standard and uses the Simple Knowledge Organization System (SKOS) as the application of the thesaurus in the web environment. Basic concepts or related terms and relationships between concepts have been linked with similar concepts in other thesauri that have existed before. This research also looks at the process of automating the recognition of related terms in internet articles using Word2Vec and Doc2Vec. In the process of adding terms, we discover challenges in filtering terms, determining relationships between terms, and determining reciprocal relationships between terms.